Association of Serum Uric Acid Levels in Psoriasis: A Systematic Review and Meta-Analysis. Issue 19 (May 2016) - Li, Xin; Miao, Xiao; Wang, Hongshen; Wang, Yifei; Li, Fulun; Yang, Qiong; Cui, Rutao; Li, Bin
Abstract : Abstract: High levels of serum uric acid (SUAC) are frequently detected in patients with psoriasis. However, the relationship between psoriasis and hyperuricemia remains unknown. Here we conducted a meta-analysis to identify the SUAC levels in subjects with psoriasis and to determine whether there is an associated risk between psoriasis and hyperuricemia. A comprehensive search of the literature from January 1980 to November 2014 across 7 databases (MEDLINE, Embase, Cochrane Central Register, and 4 Chinese databases) was conducted to determine whether there is an associated risk between psoriasis and hyperuricemia. Among the 170 identified reports, 14 observational studies were included in this meta-analysis. We found a significant higher SUAC level (MD 0.68, 95% CI 0.26–1.09; P = 0.002) in patients with psoriasis in Western Europe, but no significant differences were found between the East Asia and India subgroup (MD 1.22, 95% CI –0.13–2.56; P = 0.08) or the Middle East subgroup (MD 0.48, 95% CI –0.49–1.44; P = 0.33). Similar results were obtained from the meta-analysis of SUAC levels in subjects with severe psoriasis. Our meta-analysis showed that the correlation between psoriasis and hyperuricemia was either ethnicity- or region-dependent and that patients with psoriasis in Western Europe were more likely to have hyperuricemia.